Psychosocial factors associated with unconventional political participation in a sample of young citizens in Lima, Peru - Tintaya Orihuela, Meir Álvaro (2021)
Young Political Participation (PP) has been limited to a representative domain, and young Peruvians have been cataloged as politically disinterested and apathetic with their civic commitment to society, without inquiring about other types of political participation. Thus, from a psychosocial approach, two studies were conducted: the first seeks to (1) explore the typology, attributions and motivations of PP; (2) the second study analyzes the relationships between socio-cognitive factors (Political Knowledge, Political Interest, and Political Efficacy), attitudes (Political Trust and Political Cynism), and emotions linked to non-conventional PP in a sample of 18- to-25-year-old people of Lima, Peru. In the first study, eight interviews were conducted with young people affiliated to civil organizations, whose responses were analyzed from a thematic analysis approach. From these qualitative results, three main themes were identified: (1) a conception of political participation, (2) the motives for political participation, (3) the risks and limitations of political participation. In case of the second research, 132 youths in Lima participated in an online survey, which was submitted to correlational analyses, multiple regressions and path analysis. These results suggest two types of non-conventional PP: an contentious PP and civic-expressive PP, the latter of which is explained by political cynism and political efficacy, mediated by political interest. Implications and importance of results are discussed in relation to human development, political involvement and construction of citizenship among young Peruvians.